2016
DOI: 10.1002/ccd.26776
|View full text |Cite
|
Sign up to set email alerts
|

The impact of delirium on healthcare utilization and survival after transcatheter aortic valve replacement

Abstract: Delirium occurs in one out of five patients after trans-catheter aortic valve replacement and is associated with diminished survival and increased healthcare utilization. Further studies are needed to clarify whether strategies aimed at reducing delirium after trans-catheter aortic valve replacement may improve outcomes in this high-risk subset. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
47
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 20 publications
7
47
1
Order By: Relevance
“…Several hypotheses have been postulated, including neurotransmitter imbalances, inflammatory processes, and physiologic stress. Advanced age and multiple comorbidities are also known risk factors for development of delirium, although we could not find associations between incidence of IHPOD after TAVR and mean age, percentage of participants treated with non‐TF access, and logistic EuroSCORE. Our metaregression was performed at the study level, with lack of participant‐level data; thus, considering the mean values of tested variables (and not individual data) from included studies; such limitations may have reduced the power of our metaregression to find similar associations.…”
Section: Discussioncontrasting
confidence: 69%
See 3 more Smart Citations
“…Several hypotheses have been postulated, including neurotransmitter imbalances, inflammatory processes, and physiologic stress. Advanced age and multiple comorbidities are also known risk factors for development of delirium, although we could not find associations between incidence of IHPOD after TAVR and mean age, percentage of participants treated with non‐TF access, and logistic EuroSCORE. Our metaregression was performed at the study level, with lack of participant‐level data; thus, considering the mean values of tested variables (and not individual data) from included studies; such limitations may have reduced the power of our metaregression to find similar associations.…”
Section: Discussioncontrasting
confidence: 69%
“…The majority of participants included in our meta‐analysis were derived from 2 large prospective registries, with the lack of information regarding delirium diagnostic criteria and timing of the delirium screening . Interestingly, while these 2 large studies reported lower incidence of IHPOD after TAVR (e.g., 3.8% and 4.6%), small studies included in our analysis report higher incidence of IHPOD after TAVR . Several participant‐ and procedural‐related factors, including age at admission, comorbid condition, TAVR access, and hospital complication rate, could explain the differences in the incidence of IHPOD between these studies.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…In addition to being a psychological stress for both patients and families, delirium care in the elderly can be resource intensive and may prolong hospital or ICU length of stay (LoS) . For patients with severe aortic stenosis, TAVR is a less invasive procedure than SAVR and may have advantages in terms of reducing the likelihood of post‐AVR delirium in at risk patients . The purpose of this study was therefore to evaluate the independent incremental effect of post‐AVR delirium on hospital resource utilization in both endovascular TAVR and SAVR patients in the United States.…”
Section: Introductionmentioning
confidence: 99%